The effects of medium chain fatty acids in mash and pelleted diets on growth performance of broilers - Nichols, Gage E.; Stark, Charles R.; Delfelder, C.J.; Beyer, R. Scott; Braun, Michaela B.; Wecker, H.K.; Evans, C.E.; Woodworth, Jason C.; Jones, Cassandra K.; Paulk, Chad B. (My University, 2018)
The objective of this experiment was to determine the effects of medium chain fatty acids (MCFA) in mash and crumbled broiler diets. A total of 400 male chicks (Cobb 500; initial BW 41.8 g) were housed in 4 Petersime batteries and used in an 18-d study. Treatments were randomly assigned to 80 cages within location block resulting in 8 cages per treatment with 5 chicks per cage at placement. Treatments were arranged in a 2 × 5 factorial with main effects of feed type (mash and crumble) and 0.5% Medium Chain Fatty Acid inclusion (Control no inclusion; Hexanoic Acid (C6); Octanoic Acid (C8); Decanoic Acid (C10); Dodeanoic Acid (C12)). Fat inclusion in the diets were equalized using 0.5% soybean oil in the control diet. Feed was pelleted using a CPM (model CL5) pellet mill equipped with a 3.97×2.22 mm die. Feed was pelleted at a conditioning temperature and retention time of 85°C and 20 sec, respectively. Dietary treatments were fed for the full duration of the study. Data was analyzed as a randomized complete block design using the PROC MIXED procedure of SAS. Results were considered significant at P ≤ 0.05 and marginally significant between P > 0.05 and P ≤ 0.10. For d 0 to 12 and d 0 to 18, there were no feed form × MCFA interactions. From d 0 to 12, broilers fed crumbles had improved (P < 0.05) ADG, ADFI, FCR, and d 12 BW compared to those fed mash diets. Chicks fed C6 had increased (P < 0.05) FCR compared to those fed the control and diets containing C8 or C10. From d 0 to 18, chicks fed pelleted diets had improved (P < 0.001) ADG, ADFI, FCR, and final BW compared to those fed mash diets. For the overall treatment period there was no MCFA effect (P > 0.10) on broiler performance. Pelleting and crumbling feed improved growth performance regardless of MCFA inclusion. MCFA inclusion did not positively influence growth performance.
Keywords: Spring 2018